Synthesis, Optical Characterization, and Adsorption of Novel Hexavalent Chromium and Total Chromium Sorbent: A Fabrication of Mulberry Stem Biochar/Mn-Fe Binary Oxide Composite via Response Surface Methodology - Xu, Shuiping; Liang, Meina; Ding, Yanmei; Wang, Dunqiu; Zhu, Yinian; Han, Linbo (Frontiers in Environmental Chemistry, 2021)
In this study, a new generation chromium sorbent, mulberry stem biochar/Mn-Fe binary oxide composite (MBC-MFC), was fabricated by chemical precipitation on carbonized mulberry stem according to response surface methodology (RSM) results. RSM was more convenient to figure out the optimized preparation condition of MBC-MFC theoretically for achieving a maximum removal efficiency of Cr(VI) and total chromium (TCr), compared to labor-intensive orthogonal experiments. The RSM results showed that Fe/Mn concentration (CFe; CMn), MBC activation temperature after soaking in KOH solution (T), and pH during precipitation of Fe-Mn oxide were three main factors to significantly affect the efficiency of MBC-MFC (p < 0.05) in Cr(VI) and TCr removal. With the selected condition (CFe = 0.28 mol/L; CMn = 0.14 mol/L; T = 790°C; pH = 9.0), MBC-MFC was synthesized with a large surface area (318.53 m2/g), and the point of zero charge values of MBC-MFC was 5.64. The fabricated MBC-MFC showed excellent adsorption performance of Cr(VI) and TCr in an aqueous solution. The maximum Cr(VI) and TCr removal capacity of MBC-MFC was 56.18 and 54.97 mg/g (T = 25°C, pH = 3.0, t = 48 h, and dosage = 0.10 g/50 ml), respectively, and the maximum Cr(VI) adsorption of MBC-MFC was 4.16 times that of bare MBC, suggesting the synergistic effects of Fe/Mn oxides and MB on the performance of MBC-MFC in Cr(VI) and TCr removal. The adsorption mechanism of MBC-MFC on chromium was mainly contributed by surface complexation and electrostatic attraction. Our study offers valuable outlooks to develop high-performance biochar-based sorbents for heavy metal removal and sustainable environmental remediation.